Thermal Properties and Ionic Conductivity of Tetra-n-Butylammonium Perchlorate - Nikolai F. Uvarov (Crystals, 2022)
The thermal parameters of the phase transitions and transport properties of tetra-n-butylammonium (TBA) perchlorate (n-C4H9)4NClO4 (TBAClO4) were investigated. TBAClO4 has a polymorphous transition at 330 K and melts at 487 K. The structure of the high-temperature (HT) phase belongs to cubic symmetry and is similar to the HT phases of TBABF4 and TBAI salts. The conductivity parameters of the low-temperature and HT phases of TBAClO4 were determined from the Arrhenius plots. The thermodynamic parameters and transport properties of TBAClO4 were compared with those of other TBA salts having isostructural HT phases. The polymorphous phase transition entropy was found to correlate with the conductivity of HT phases of TBA salts; TBAClO4 has the lowest conductivity compared to TBABF4 and TBAI salts.